Forma contractual y desarmonización comunitaria - Santos Morón, María José (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
The EC consumer contract law establishes numerous provisions relating to form. Nevertheless, in this area the Directives havent caused a real harmonization. The sanctions established for non-compliance with formal requirements in each State are very different. Although developing a general rule with regard to remedies applicable in case of breach of contract form would have been suitable, neither the ACQP nor the DCFR contain any rule about it. On the other hand, the Proposal for a directive on Consumer Rights introduces new formal requirements regarding to off-premises contracts, which should be criticized. This paper aims to provide a sanction that may be applied in all cases of breach of formal requirements in the attempt of making a proposal for future harmonization.
Keywords: Formal requirements; written form; consumer protection; contractual information duty; non-compliance with formal requirements; diversity of sanctions; right to withdrawal